IN VITRO EVALUATION OF THE ANTIFUNGAL ACTIVITY OF ETHANOL EXTRACT COMBINATIONS OF SOURSOP (Annona muricata) AND RED DRAGON FRUIT (Hylocereus polyrhizus) PEELS AGAINST Candida albicans - yulia, inelvi; nurmiati, Nurmiati; haq, ruqaya annisa nurul; putri, nespi widia (E-Jurnal Medika Udayana, 2025)
Candida albicans is a common commensal microorganism found on the skin, genital organs, oral cavity, and various other parts of the human body. However, its population can increase excessively due to inappropriate use of antibiotics without medical supervision and weakened immune function. One of the clinical manifestations caused by C. albicans overgrowth is pathological vaginal discharge, which may lead to more serious complications if left untreated. While commercial antifungal agents are available, they are often associated with side effects such as a burning sensation, nausea, and vomiting. Natural alternatives, including bioactive compounds from plant materials, are increasingly being explored for their antimicrobial properties. Soursop ( Annona muricata ) and red dragon fruit ( Hylocereus polyrhizus ) peels have been reported to contain such bioactive compounds with potential antimicrobial effects. The aim of this study was to evaluate the in vitro antifungal activity of combined ethanol extracts of soursop and red dragon fruit peels against Candida albicans . This laboratory-based experimental study used a one-way analysis of variance (ANOVA) to assess differences in antifungal activity among extract combinations. The results showed that combinations I (1:1), II (1:2), and III (2:1) of the extracts produced inhibition zones of 14.0 mm, 15.0 mm, and 20.1 mm, respectively. These inhibition zones are classified as strong to very strong based on standard antimicrobial activity categories. In conclusion, the combination of ethanol extracts from soursop and red dragon fruit peels demonstrated significant in vitro antifungal activity against Candida albicans . These findings support the potential use of natural plant-based antifungal agents as alternative or complementary treatments for candidiasis. Keywords : Dragon fruit peel and soursop peel; Candida albicans; inhibition zone; in vitro